Inovasi Pangan Lokal melalui Pembuatan Tempe Berbahan Dasar Varian Kacang-Kacangan - Nonci M. Uki; Meti O. F. I. Tefu; Adi B. W. Banu; Christian Lasi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Bijeli Village in the Polen District of South Central Timor Regency possesses abundant local legume resources such as small red beans, large red beans, and peanuts yet their utilization remains limited to traditional food consumption without generating significant economic value. This Community Service (PkM) initiative aimed to enhance the community's knowledge and skills in processing these local legumes into tempeh as an alternative to soybean-based tempeh, thereby supporting food diversification based on local potential. The program comprised several stages: outreach, demonstrations, tempeh-making training, ongoing guidance, and evaluation via organoleptic testing of the three tempeh varieties. Twenty residents of Bijeli Village participated in the activities. Participants demonstrated high enthusiasm and active engagement, indicating an improvement in their understanding and proficiency regarding the production of tempeh from local legumes. Organoleptic test results revealed that small red bean tempeh achieved the highest acceptance ratings for taste, aroma, and texture; furthermore, 70% of respondents identified it as the product with the greatest potential for further development. These findings demonstrate that small red beans hold significant promise as a raw material for nutritious, high-quality alternative tempeh. Consequently, this initiative contributes tangibly to strengthening local food security and empowering the Bijeli Village community through food diversification and the enhancement of agricultural commodity value.